Art and authority : aspects of Russian art since 1917 - Thompson, Rowan Douglas (Rhodes University, Faculty of Humanities, Department of Fine Art, 1991)
From Introduction: The Artist was denied any role in Plato's Republic because of his ability to impair reason by imitating reality through his works. Aristotle, however, welcomed the artist because of his ability to express ideas about society through artistic form. Ernst Fischer agrees with the latter view, "Art enables man to comprehend reality, and not only helps him to bear it but increases his determination to make it more human and more worthy of mankind. Art is itself a social reality, society needs the artist ... and it has a right to demand of him that he should be conscious of his social function" (Fischer: 1963:46). Fischer adds to Aristotle's view by stating that society has a right to demand a social function from the artist. This issue has been the subject of controversial debate throughout the history of art. In a society based on class, the classes try to recruit art to serve their particular purposes. Art is seen by some as a powerful weapon - a means by which people can be swayed towards certain ideals. At the time of the Counter Reformation Italian artists were given strict instructions by the Jesuits on how to persuade and educate the people with their paintings. Napoleon urged his men of letters, painters and architects to refer to the classical ideals of ancient Greece and Rome to shape the emergent French Republic. The French philosopher, Dennis Diderot, stressed the futility of art unless it expressed great prinCiples or lessons for the spectator. Ideals of justice, courage and patriotism were embodied in the Neo-Classical movement. The didactic paintings of Jacques Louis David portray the above ideals. History records several attempts by those in power to coerce artists into conforming to their idea of society, indicating that authoritative manipulation of the arts is not purely a twentieth century phenomenon. This thesis intends to examine aspects of Russian art since 1917. Because Soviet art was dominated by policies which enabled authorities to determine its content, its history raises ideological issues which are relevant to the study of art. The theories of Suprematism, Constructivism and Socialist Realism will be discussed and conclusions will be drawn as to whether these theories succeeded as art movements which were ostensibly designed for the improvement of mankind. Present attitudes toward the visual arts in Russia will also be examined. However, in order to examine the above it is necessary to place the development of art into historical perspective.
Keywords: Authority in art; Art, Russian; Art, Russian -- 20th century